CYTOLOGY PULMONARY IN HORSES (EQUUS CABALLUS) MAINTAINED THE FIELD OR STABLED - W. F. Fortes Júnior; R. C. A. Berber; T. V. Souza; A. C. Rosa; I. Deconto (Scientific Electronic Archives, 2016)
Tracheobronchial secretion was collected by endoscopy (Welch-AllynÒ, 200cm long and 9mm diameter), from equines with different ages, races and sex, for posterior cytological analysis. Thirty-six equines were divided into two groups (Group I = stabled, n = 18; Group II = field regimen, n = 18). Animals of Group I (age = 3.5 years) were lodged in the Tarumã´s Jockey Club in Curitiba, Parana State. The equines of Group II always were maintained at field condition (never were stabled), in the farm located in Jacarezinho, Paraná State. Following endoscopic exams, tracheobronchial secretion smears were stained by Pappenhein´s method and submitted to cytological analysis. Group I had higher frequency of tracheal discharge than Group II. The cytological analysis showed more presence of macrophages (58.8%), foamy cells (2.3%), body giant cells (0.2%), neutrophils (4.57%), eosinophils (0.7%) and Curshmann´s spirals (0.04%) on 3 of the 18 animals. The cytological analysis of Group II showed higher frequency of ciliated epithelial cells than Group I, and no Curshmann´s spirals were observed. In conclusion, data showed that horses stabled had more cytological alterations than the animals maintained at field, therefore more tracheobronchial complications. Thus, the care of place where horse are stabled have influence on development of respiratory diseases, may predispose to affections as Chronic Obstructive Pulmonary Disease and Exercise-Induced Pulmonary Hemorrhage, as well athletic horses may be never reach their full respiratory potential.